INVESTIGATION OF SORPTION CHARACTERISTICS OF ANAEROBICALLY DIGESTED DEWATERED MUNICIPAL SEWAGE SLUDGE - Varank, Gamze; Demir, Ahmet; Bilgili, M. Sinan; Top, Selin; Sekman, Elif; Yazici, Senem; Erkan, Hanife Sari (TECHNICAL UNIV WROCLAW, 2014)
Physical, chemical, morphological properties and sorption characteristics of anaerobically digested dewatered municipal sewage sludge have been investigated including the surface area, pore size distribution, chemical composition, surface chemistry structure, surface physical morphology, mineralogy, cation exchange capacity, heavy metal content, total solid, total volatile solid, total Kjeldahl-N, total phosphorus content of the sewage sludge. The sorption potential of sewage sludge for the removal of 4-CP and 2,4-DCP from aqueous solutions was examined by investigating their adsorption isotherms and kinetics in a lab-scale batch study. Findings of this study clearly showed that sewage sludge provides chlorophenol removal in the landfill body as disposed with solid wastes.
Keywords: ADSORBENTS; REMOVAL; ADSORPTION; COPPER; AREA; LEAD; Engineering